Smooth as butter: A discourse analysis of Adam Ragusea’s seamless sponsorship segues as an art of marketing scriptwriting - Erina Andriani (Indonesian Journal of English Language Studies (IJELS), 2026)
With the surge in social media creators and influencers, brands and companies have increasingly collaborated with them to extend their reach to mass audiences on social media platforms through sponsored segments. Transitioning from the main video content to the sponsorship showcases the language’s role in retaining the audience’s attention and interest. Examining Adam Ragusea’s sponsorship segues, this article aims to dissect the idea flows and transition tools to seamlessly integrate sponsorship in content videos. This study conducted Fraser’s Taxonomy-based discourse analysis of the sponsorship segment in 45 recipes and food science videos, selected using purposive sampling. The research found 10 types of idea flows that served as the segues into and out of the sponsorship segment, namely storytelling, cause-effect, comparison, problem-solution, repetition, need-solution, dissociation, analogy, contrast, and metaphor. It also found six transition tools unique to the specific idea flows, namely contrastive, elaborative, and inferential discourse markers, along with filler words, comparison, and visual-based transitions. Strategically utilizing different idea flows in the sponsorship segues can serve various creative narratives to maintain engagement, enhancing the effectiveness of the social media marketing for brands and content creators in terms of message relevance and reach.